Correction: Akintade, D.D.; Chaudhuri, B. Apoptosis, Induced by Human α-Synuclein in Yeast, Can Occur Independent of Functional Mitochondria. Cells 2020, 9, 2203 - Damilare D. Akintade; Bhabatosh Chaudhuri (Cells, 2025)
In the original publication [...]